Perilaku gizi dan hidrasi selama kehamilan berhubungan dengan konstipasi - Palupi, Khairizka Citra; Sa’pang, Mertien; Mulyani, Erry Yudhya; Laili, Aditya Fatkhi (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2020)
Background: Prevalence of constipation in pregnant women is estimated at 11-38%. Impact of constipation in pregnant women are haemorrhoids and decreased quality of life. Meanwhile, determinants known to influence constipation during pregnancy are hormonal changes, poor diet, low physical activity and lack of fluid consumption. Objectives: Identify the determining factors that can affect occurrence of constipation and investigated the difference based on constipation status among pregnant women in Public Health Centre in Jakarta, Indonesia;Methods: This research was a cross sectional design conducted in July 2019 to October 2019. The subject was pregnant women. We used accidental sampling method to recruit subjects in Public Health Centre, Kebun Jeruk, West Jakarta. We measured the determining factors of constipation among pregnant women. Characteristic of pregnant women, knowledge, attitudes and practices were measured by questionnaires. Anthropometrics data for weight, height, and mid arm circumference were measured. Haemoglobin level was also measured. Bivariate analysis using Pearson or Spearman was used to investigate which factors associated significantly with constipation among pregnant women. We also assessed the difference of characteristic of pregnant women, knowledge, attitudes and practices using differential analysis (Mann-Whitney U-test). Results: The results showed that prevalence of constipation was 30%. Differential analysis showed that mothers who experienced constipation had a younger age and low nutritional and hydration behaviour scores. Other variables such as gestational age, weight before pregnancy, upper arm circumference, height, haemoglobin, knowledge score and nutritional attitude and hydration did not show significant differences based on constipation status. Correlation analysis showed an inverse relationship between maternal age and incidence of constipation, with r = 0.242 and a p-value = 0.015. Maternal age, nutritional behaviour and hydration also showed significant inverse relationship with incidence of constipation (r = -0.206 and p-value 0.039);Conclusion: Nutritional and hydration behaviour during pregnancy was related to the occurrence of constipation. Mothers are advised to have good nutrition and hydration behaviour to prevent constipation.